Capital Market Reaction towards 2024-2029 Republic of Indonesia’s Presidential & Vice Presidential Inauguration - Effendy, Anderson Jonathan; Santoso, Tiara Rani; Najmuddin, Ahmad Bebin (E-Jurnal Akuntansi, 2025)
This research was intended to examine the Indonesian financial market's response towards 2024 Presidential inauguration. Using a quantitative approach, the study employs an event study methodology with a 14-day observation period, comprising 7 days prior to and 7 days following the inauguration. It evaluates abnormal returns and trading volume activity during this timeframe. This research focuses on 45 corporations inside the LQ-45 index, with data taken from BEI website. Wilcoxon signed-rank test was used as Hypothesis test method with the results indicating no significant changes in abnormal returns pre- and post-event, but a significant negative change was observed in trading volume activity. This suggests a negative market reaction to the event, as evidenced by reduced trading activity after the inauguration. Keywords: Presidential Inauguration; Stock Prices; Trading Volume Activity; Abnormal Return